1999
DOI: 10.2134/agronj1999.00021962009100020026x
|View full text |Cite
|
Sign up to set email alerts
|

Spring‐Applied Nitrogen and Productivity of Cool‐Season Grass Seed Crops

Abstract: Understanding effects of spring N rates and application timing on seed yield and yield components of cool‐season grass seed crops will help improve N fertilization management. We tested effects of 90, 120, 150, 180, and 210 kg N ha−1, applied at the double‐ridge (DR) stage of development on seed yield and yield components of Chewing's fescue [Festuca rubra L.subsp. fallax (Thuill.) Nyman; syn. F. rubra var. commutata Gaudin], tall fescue (F. arundinacea Schreb.), and orchardgrass (Dactylis glomerata L.) in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
3
12
1
Order By: Relevance
“…The SEM indicated that the number of fertile tillers m −2 contributed most to seed yield. The present findings differ from previous reports indicating that seed number spike −1 and seed weight were the most important yield components for seed yields of perennial ryegrass and orchardgrass (Hebblethwaite and Ivins, 1977; Young et al, 1996, 1999). However, the results of the current study are similar to those of several studies showing that spike number unit area −1 was the most important yield component for seed yield in red fescues ( Festuca rubra L.) (Meints et al, 2001), smooth brome ( Bromus inermis L.) (Wang et al, 2004), and perennial ryegrass (Deleuran and Boelt, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…The SEM indicated that the number of fertile tillers m −2 contributed most to seed yield. The present findings differ from previous reports indicating that seed number spike −1 and seed weight were the most important yield components for seed yields of perennial ryegrass and orchardgrass (Hebblethwaite and Ivins, 1977; Young et al, 1996, 1999). However, the results of the current study are similar to those of several studies showing that spike number unit area −1 was the most important yield component for seed yield in red fescues ( Festuca rubra L.) (Meints et al, 2001), smooth brome ( Bromus inermis L.) (Wang et al, 2004), and perennial ryegrass (Deleuran and Boelt, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…This phenomenon was also observed by Young et al (1999), who reported that N addition had a positive eff ect on orchardgrasss (Dactylis glomerata L.) seed yield and total dry weight of harvested reproductive structures (registered before threshing); however, tall fescue (Festuca arundinacea Schreb.) By contrast, seed production had a negative (−69%) relationship with the proportion of fi lled seed at Beeville in November 2005.…”
Section: Proportion Of Filled Seedsupporting
confidence: 68%
“…However, this variable was not related to seed yield at Beeville in May and October 2006. This phenomenon was also observed by Young et al (1999), who reported that N addition had a positive eff ect on orchardgrasss (Dactylis glomerata L.) seed yield and total dry weight of harvested reproductive structures (registered before threshing); however, tall fescue (Festuca arundinacea Schreb.) seed production was unaff ected while increasing total dry weight of those structures, indicating that seed yield is not necessarily related to the total dry weight of the harvested material and that other seed yield components may be responsible for seed yield changes.…”
Section: Proportion Of Filled Seedsupporting
confidence: 68%
“…As one of the most important nutrients affecting seed yield in grasses (Rolston et al, 1985), N application has a substantial effect on seed number per inflorescence and seed weight (Hebblethwaite and Ivins, 1977; Young et al, 1996, 1999; Cookson et al, 2001; Wang et al, 2010) but no influence on inflorescence number (Hampton and Hebblethwaite, 1983; Young et al, 1996). In the present study, the timing and rate of fall N applications not only had a significant effect on seed number per inflorescence and 1000‐seed weight but also on inflorescence number (Table 1).…”
Section: Discussionmentioning
confidence: 99%